Business intelligence as a knowledge management tool in providing financial consultancy services - Muhammad, Gul; Ibrahim, Jamaludin; Bhatti, Zeeshan; Waqas, Ahmad (Science and Education Publishing, 2014)
The main objective of this paper is to elaborate how Business Intelligence (BI) as a knowledge management tool could help consultants in providing professional services to the financial sector. The Business Intelligence (BI) solution could be a competitive advantage for the consultants if they are able to exploit the Business Intelligence (BI) tools and technology such as Data Warehouse, Data Mining, On-Line Analytical Processing (OLAP) and Extraction Transformation Load (ETL). The consultants can use Business Intelligence (BI) solution to analyze the organizational data such as structures and business processes of the Financial Institution. By analyzing the organizational data, the financial institution can imp better rove and streamline functional efficiencies to not only bolster up sales and marketing strategies and better develop customer services program, but also mitigate risk by developing more appropriate risk management actions. In brief, by having this competitive advantage, the consultant will be able to withstand in the market, which is always changing.